A portrait of the artist as a young man - Joyce, James, 1882-1941. (Oxford ; New York : Oxford University Press, 2008)
An autobiographical novel depicting the childhood, adolescence, and early manhood of Stephen Dedalus.
Includes bibliographical references.
Adult.
Adult
Keywords: Artists -- Ireland -- Dublin -- Fiction; Dedalus, Stephen (Fictitious character) -- Fiction; Young men -- Ireland -- Dublin -- Fiction; Artists -- Dublin (Ireland) -- Fiction; Autobiographical fiction; Bildungsromans; Dedalus, Stephen (Fictional character) -- Fiction; Young men -- Dublin (Ireland) -- Fiction; Dublin (Ireland) -- Fiction; Dublin (Ireland) -- Fiction; Autobiographical fiction; Bildungsromans